Teacher strategies in teaching reading to the 8th grade students of a private junior high school in Bandung - Ervan Fauzan; Rahma Sakina; Riyadh Ahsanul Arifin; Sri Yunita (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2024)
Teaching reading is one of the skills that must be mastered in English which aims to get a meaning from a text. There are several kinds of methods and strategies that can be used to teach reading. This research focused on what strategies are used by teachers, the challenges that arise when using these strategies, and how teachers overcome these challenges. In this study, researcher used descriptive qualitative study with observation and interview data collection. This research was conducted at a private junior high school in Bandung and the participants are an English teacher and 28 students of grade 8. The results of this study are classified into 3 themes: strategies used by teachers in teaching reading, challenges faced when implementing strategies, and how the teacher to overcome these challenges. It was found that the teacher used 3 strategies in teaching reading, namely Question Answer Relationship, Scaffolding, and Reading Aloud. Teacher found several challenges, namely students' low communication skills, the lack of supported facility, and the lack of students' vocabularies, and student response to length of the text. The teacher overcomes some of these challenges, namely using a mix language of English and Bahasa, the teacher used a good approach when learning, and the teacher masters all the material so that when students ask questions the teacher can answer all the questions. For the further researcher will add more sources or references related to teaching reading, so the results of the research more complete.